Dose–response, therapeutic time-window and tPA-combinatorial efficacy of compound 21: A randomized, blinded preclinical trial in a rat model of thromboembolic stroke. Issue 8 (August 2019) - Ishrat, Tauheed; Fouda, Abdelrahman Y; Pillai, Bindu; Eldahshan, Wael; Ahmed, Heba; Waller, Jennifer L; Ergul, Adviye; Fagan, Susan C
The aim of this translational, randomized, controlled, blinded preclinical trial was to determine the effect of compound 21 (C21) in embolic stroke. Rats were subjected to embolic-middle cerebral artery occlusion (eMCAO). They received C21 (0.01, 0.03 and 0.06 mg/kg/d) or saline (orally) for five days, with the first-dose given IV at 3 h post-eMCAO. For the time-window study, the optimal-dose of C21 was initiated at 3, 6 or 24 h post-eMCAO and continued for five days. For the combinatorial study, animals received IV-tissue plasminogen activator (tPA) at either 2 or 4 h, with IV-C21 (0.01 mg/kg) or saline at 3 h post-eMCAO and daily thereafter for five days. After performing the behavior tests, brains were collected for analyses. The dose–response study showed significant motor improvements with the lowest-dose (0.01 mg/kg) of C21. In the time-window study, this same dose resulted in improvements when given 6 h and 24 h post-eMCAO. Moreover, C21-treated animals performed better on the novel object recognition test. Neither the single treatment with C21 or tPA (4 h) nor the combination therapy was effective in reducing the hemorrhage or infarct size, although C21 alone lowered sensorimotor deficit scores post-eMCAO. Future studies should focus on the long-term cognitive benefits of C21, rather than acute neuroprotection.